(3SdSdI JQLeGJ CefjI(B. 1 / (3JQLeI aQjb Yed eQcR GdHMhK h GdOQGSGJ, CcGOjejI TQWI OHj ; ETQa NGdO NdaGf CMeO GdefUhQj(B.s - (3efUhQj, NGdO NdaGf CMeO(B.s ((3OHj (B: s (3eQcR GdHMhK h GdOQGSGJ HCcGOjejI TQWI OHj, s, 2013)
(3fXQG dchf GdJQLeI EMOi hSGFd fbd GdJLGQH ef dSGf Edi BNQ djSgd Hg HjGf GdeYGfj hdJROGO Hg MUjdI GdeYGQa, hdCf GdZQH SHGbkG aj eLGd GdYdhe HUaI YGeI haj Yde GdLQjeI HUaI NGUI hdCgejI ecGaMI GdLQjeI, aj YUQfG GdMGdj(B. (3GQJCi eQcR GdHMhK hGdOQGSGJ aj CcGOjejI TQWI OHj, YHQ aQb GdYed GdOGNdjI, Cf jbhe HJQLeI CLRGA dHYV GdeDdaGJ hGdCHMGK GdCefjI GdeJejRI hYed edNUGJ dHYV GdEUOGQGJ GdegeI aj eLGd GdMO ef GdLQjeI hPdc dZGjI fbd JLGQH GdBNQjf aj gPG GdeLGd hdJfejI MUjdI GdeYQaI GdYdejI ddbGQF GdYQHj aj SdSdI JQLeGJ CefjI JMJhj Ydi JQLeI (B8 (3ebGdGJ YdejI CefjI h (B6 (3edNUGJ dcJH CefjI eJNUUI(B.s
Keywords: (3GdLQjeI h GdeLQehf s -- (3ebGdGJ h eMGVQGJ(B. s; (3GdLQjeI h GdeLQehfs -- (3JQLeI Edi GdYQHjI(B. s; (3GdYfa s -- (3JQLeI Edi GdYQHjI(B. s